Bacteriological Profile and Antibiotic Sensitivity Pattern of Neonatal Sepsis in Central Paediatric Referral Hospital in Nepal - Bhattarai, Susan; Chapagain, Ram Hari; Mishra, Deepak; Shrestha, Anil Kumar; Shrestha, Sushan Man (Journal of Nepal Paediatric Society, 2019)
Introduction: Neonatal sepsis is the most common cause of neonatal morbidity and mortality. The causative organisms of neonatal sepsis are changing and so do their antibiotic sensitivity pattern. So it is important to regularly monitor the change in bacteriological profile and their antimicrobial sensitivity pattern to help update the treatment guidelines of neonates. This study aimed to study the microbiological patterns of neonatal sepsis and their antibiotic susceptibility pattern in a tertiary care centre in Kathmandu. Methods: A prospective study was carried out among cases of neonatal sepsis admitted in Neonatal Intermediate Care Unit (NIMCU) of a tertiary care referral hospital from August 2015 to August 2016. Prospective data were collected with pretested and standardised proforma and analysed using SPSS version 20. Results: Out of 311 neonates admitted over a period of one year with diagnosis of neonatal sepsis, male:female ratio was 2.1:1. Among them 234 (75.2%) cases were of LONS and 77 (24.8%) were of EONS. Blood culture was positive in 47 neonates (15.1%). The organisms isolated included staphylococcus aureus (34.0%), klebsiella (32%), CONS (24%), escherechia coli (6%) and enterobacter (4%). In LOS, gram positive organisms staphylococcus and CONS were the commonest ones (61.4%). In EOS, gram negative organism klebsiella (65%) was more common. Most of staph aureus were susceptible to penicillins, amikacin and cefotaxime. Klebsiella was found to be resistant to penicillins, amikacin and cefotaxime. Conclusion: There is possible increasing incidence of gram positive septicemia in LONS and increasing emergence of resistance of kleibsella to the common antibiotics ampicillin, amikacin and cefotaxime.